Literature Review Faktor Penyebab Ketidaklengkapan Pengisian Dokumen Rekam Medis Dengan Metode Fishbone: Review Faktor Penyebab Ketidaklengkapan Pengisian Dokumen Rekam Medis Dengan Metode Fishbone - Muhammad Ghani Pratama; Nunik Maya Hastuti (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2022)
ABSTRACT Background: Based on articles other than those studied, incomplete medical record documents were found. The incomplete filling of medical record documents is certainly caused by several factors. To find out some of these factors the researchers looked at using themethod fishbone. This incompleteness attracted researchers to take the title